Contrasting interactions between photon spectra and temperature in cold-sensitive basil and cold-tolerant lettuce - Shin, Jiyong; Bugbee, Bruce; Runkle, Erik S. (Frontiers in Plant Science, 2025)
Blue (B; 400–499 nm) light, far-red (FR; 700–750 nm) light, and temperature are key regulators of plant growth and development, with responses varying by species. While the independent effects of these environmental signals are well established, their interactive effects are not clear. We postulated that the effects of FR light and temperature would depend on the photon flux density (PFD) of B light. To test this, we grew cold-tolerant lettuce and cold-sensitive basil at 19 and 24°C under lighting treatments with three FR fractions [FR-PFD divided by the sum of red (600–699 nm) and FR PFD; 0.01, 0.19, or 0.32] and two B-PFDs (40 or 100 µmol m−2 s−1). The total PFD (400–750 nm; 270 µmol m−2 s−1) and photoperiod (24 h d−1) were the same in all treatments. There were significant differences between species. As expected, increasing the FR fraction dramatically increased shoot expansion in lettuce and internode elongation in basil. The shoot expansion in lettuce was amplified by higher temperature but attenuated by higher B-PFD. Unlike lettuce, the FR effect on basil internodes did not interact with either temperature or B-PFD. The increased shoot expansion in lettuce decreased foliage coloration, but coloration was minimally altered in basil. These results reveal fundamentally different species responses to light and temperature that may have implications for shade-avoidant and shade-tolerant species. Overall, these findings demonstrate the complex integration of environmental signals in the regulation of growth.